2015
DOI: 10.1007/s00484-015-1066-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor heat stress variability in summer and during heat warnings: a case study using the UTCI in Berlin, Germany

Abstract: Humans spend most of their time in confined spaces and are hence primarily exposed to the direct influence of indoor climate. The Universal Thermal Climate Index (UTCI) was obtained in 31 rooms (eight buildings) in Berlin, Germany, during summer 2013 and 2014. The indoor UTCI was determined from measurements of both air temperature and relative humidity and from data of mean radiant temperature and air velocity, which were either measured or modeled. The associated outdoor UTCI was obtained through facade meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In summary, for buildings without air conditioning, which are the most common in Scandinavia, several studies have found a strong correlation between the outdoor and indoor temperature [10,11,12,13,14,15]. Furthermore, the humidity relationship between the indoor and outdoor conditions tends to be stronger than the temperature relationship [17,20,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, for buildings without air conditioning, which are the most common in Scandinavia, several studies have found a strong correlation between the outdoor and indoor temperature [10,11,12,13,14,15]. Furthermore, the humidity relationship between the indoor and outdoor conditions tends to be stronger than the temperature relationship [17,20,27].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Oudin Åström et al (2018) found that heat waves significantly increased both all-cause mortality and coronary heart disease mortality by approximately 10–15%, respectively, in the Swedish context [7]. There is especially a need for studies in developed countries, as studies about indoor environments show that the population in these countries spend most of their time—about 90%—indoors [8,9,10,11,12,13,14,15]. The health outcomes of heat exposure depend on the climatic zones specific for given regions [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Quansheng et al (2016), Matzarakis (2014), Matzarakis et al (2013), Zaninović and Matzarakis (2009), Lin and Matzarakis (2008) studied the climate from the point of view of tourism development prospects and Fr hlich and analysed the limitations and shortcomings of the three indices (PT, UTCI, PET) under the hot and windy meteorological conditions observed in Doha, Qatar. The research explored the role of street trees in Melbourne, Australia, in cooling the urban microclimate and improving human thermal comfort (HTC) were calculated using the UTCI index given by Coutts et al (2016) and Walikewitz et al (2015) which made an assessment of indoor heat stress variability in summer and during heat warnings in Berlin, Germany.…”
Section: Introductionmentioning
confidence: 99%
“…These measures seem unproblematic. However, it has also been suggested that ventilation systems not equipped with cooling could be switched off during the daytime to avoid drawing in hot air from outdoors [ 74 ]. This can be effective and justified as a short-term measure during extreme heat waves, but if commonly used it can create new adverse health effects [ 75 ].…”
Section: Themes Of Special Interest Discussed From the Perspectivementioning
confidence: 99%